Ujian Nasional (UN): Harapan, Tantangan, dan Peluang - Sulistyo, Gunadi H. (UI Scholars Hub, 2007)
The National Examination (NE) has been conducted for several times nation-wide. However, public debates always emerge over the importance of NE prior to the annual excecution of the examination. The government's policy to raise the passing standard under the pretext of improving the quality of the national education has commonly triggered a heated controversy. This paper discusses the NE from the perspectives of expectations, challenges and opportunities. It attempts to provide an objective picture as to the need to hold NE. As such, it puts the attempts to improve the quality of the national education through NE in a proportionately wider perspective.